School Integration How It Effects Black Children? - Merriweather, Rhonda ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Twenty documents discussing the beneficial effects of school desegregation, particularly on black children, and thirteen studies finding desegregation harmful are cited and their major findings and research methods described briefly in this document. Essentially an annotated bibliography, the report concludes by summarizing briefly the results of the studies cited. The author states that the research has not led to definite, agreed-upon conclusions, though it is generally held that integration increases the number of interpersonal problems faced by black students while helping them relate to their white peers academically. (PGD)
ERIC Note: Submitted in partial fulfillment of the requirements for the Master of Education degree in the Division of Education, Indiana University at South Bend.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Black Students; Desegregation Effects; Elementary Secondary Education; Integration Studies; Racial Integration; School Desegregation; Reference Materials, Bibliographies